2016
DOI: 10.1002/ccd.26428
|View full text |Cite
|
Sign up to set email alerts
|

Influence of smoking on the antiplatelet effect of clopidogrel differs according to clopidogrel dose: Insights from the GRAVITAS trial

Abstract: Smokers treated with clopidogrel exhibit reduced platelet reactivity and are less likely to have persistent high OTR than non-smokers. This difference is mitigated by clopidogrel 150 mg, indicating non-smokers may require double-dose therapy to achieve a similar antiplatelet effect after PCI. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
1
7
1
5
Order By: Relevance
“…11 In the platelet substudy of the GRAVITAS trial, the difference in platelet aggregation between smokers and nonsmokers treated with clopidogrel was observed only in patients treated with the standard dose of clopidogrel, not in those treated with the double dose. 27 This finding supports the potential use of the double dose of clopidogrel following smoking cessation. Another option would be treatment with prasugrel, which is a thienopyridine that does not share the same metabolic pathway as clopidogrel or ticagrelor, a direct-acting P2Y 12 inhibitor.…”
Section: Discussionsupporting
confidence: 61%
“…11 In the platelet substudy of the GRAVITAS trial, the difference in platelet aggregation between smokers and nonsmokers treated with clopidogrel was observed only in patients treated with the standard dose of clopidogrel, not in those treated with the double dose. 27 This finding supports the potential use of the double dose of clopidogrel following smoking cessation. Another option would be treatment with prasugrel, which is a thienopyridine that does not share the same metabolic pathway as clopidogrel or ticagrelor, a direct-acting P2Y 12 inhibitor.…”
Section: Discussionsupporting
confidence: 61%
“…In contrast, double-dose clopidogrel eliminated the difference due to smoking status, resulting in similar levels of platelet activity between smokers and non-smokers. 35 We do not encourage cigarette smoking based on the present study results. Smoking induces hypercoagulability and results in early MI, as shown in the present study.…”
Section: In-hospital Adjusted Outcomescontrasting
confidence: 53%
“…The ‘smoking paradox’ has been demonstrated in patients undergoing cardiac stents, who had lower early mortality 11. In addition, another study showed that smokers tend to have more platelet inhibition in response to clopidogrel than non-smokers 12. A meta-analysis, however, showed no effect of smoking on major cardiovascular events but an increased risk of major cardiovascular and cerebrovascular events in smokers (vs non-smokers) undergoing coronary stenting (OR 2.09, 95% CI 1.43 to 3.06) 13.…”
Section: Discussionmentioning
confidence: 99%